Estudio del clima organizacional en autoridad portuaria de Puerto Bolivar - Asanza Jiménez, Vilma Carmen (2012)
During the months of September and October of 2011, a study was made about the organizational environment at APPB, applying an instrument to the personal that works there from the Management passing by the middle management to the operative level about the perception they have about the motivation, communication, leadership and company organizational structure in thirty four questions.It was defined according to Likert scale strengths and weaknesses with the goal to formulate strategies that allow surpassing the strengths and weaknesses.As for the motivation variable, it was showed as strength, however to strengthen it, in the strategy formulation it was suggested at the moment of elaborating the improvement plan, it is incorporated the need of a better communication between the management and low levels.When analyzing the communication variable, also take as a strength, which it can be consolidated as detail in the purpose, through the realization of organizational communication workshops that motivate the manufacture.As the leadership variable, it was expressed as a strength as well, that can be strengthen as propose in the strategies of this study, where the management apply techniques to feedback the making. The organizational culture variable, it also was manifested as a strength that can be strengthen, implementing a manage system that optimize the processes y the disciplined thinking of the company. The structure strategies proposed are presented in a schedule put into consideration of the APPB for its execution, as a contribution to the improvement of the organization environment.